1997
DOI: 10.1098/rspb.1997.0023
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of wavelength tuning in the rod opsins of deep-sea fishes

Abstract: SUMMARYThe main object of this study was to investigate the molecular basis for changes in the spectral sensitivity of the visual pigments of deep-sea fishes. The four teleost species studied, Hoplostethus mediterraneus, ataet x laticeps, Gonostoma elongatum and Histiobranchus bath bius, are phylogenetically distant from each other and live at depths ranging from 500 to almost 5000 m. A single fragment of the intronless rod opsin gene was PCR-amplified from each fish and sequenced. The wavelength of peak sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 44 publications
4
61
0
Order By: Relevance
“…In the dim and spectrally restricted illumination encountered even at moderate depths, maximizing quantum catch is imperative and sensitivity will depend even on small shifts of the visual pigment absorbance spectrum. Many studies have revealed spectral adaptations between different fish species (Hunt et al, 1996;Hunt et al, 2001;Hope et al, 1997;Carleton and Kocher, 2001;Parry et al, 2005;Carleton et al, 2005;Carleton et al, 2008;Seehausen et al, 2008). However, there has been little evidence on incipient evolutionary adaptation of rod spectral sensitivity between separated populations inhabiting spectrally different waters.…”
Section: Discussion Differences In Mean  Max Between Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the dim and spectrally restricted illumination encountered even at moderate depths, maximizing quantum catch is imperative and sensitivity will depend even on small shifts of the visual pigment absorbance spectrum. Many studies have revealed spectral adaptations between different fish species (Hunt et al, 1996;Hunt et al, 2001;Hope et al, 1997;Carleton and Kocher, 2001;Parry et al, 2005;Carleton et al, 2005;Carleton et al, 2008;Seehausen et al, 2008). However, there has been little evidence on incipient evolutionary adaptation of rod spectral sensitivity between separated populations inhabiting spectrally different waters.…”
Section: Discussion Differences In Mean  Max Between Populationsmentioning
confidence: 99%
“…When going from marine to coastal, brackish or fresh water basins, the ambient light environments tends to shift from blue to green, yellow or even reddish brown, challenging the visual systems of the animals and creating a laboratory for studies on evolutionary adaptation of visual pigments (e.g. Hunt et al, 1996;Hunt et al, 2001;Hope et al, 1997;Yokoyama and Tada, 2000). The performance of rod vision is expected to depend in a straightforward manner on the degree of 'match' between the absorbance spectrum of the visual pigment and the illumination spectrum, because the visual information obtained at low light levels is critically dependent on photon catch, and rods alone convey information at these light levels.…”
Section: Introductionmentioning
confidence: 99%
“…In most animals with varying spectral receptor classes, changes occur either on evolutionary time scales (Carleton and Kocher, 2001;Cronin et al, 1996;Hope et al, 1997;Hunt et al, 1996;Lythgoe et al, 1994;McDonald and Hawryshyn, 1995;Morris et al, 1993) or concurrent with overall ontogenetic changes in physiology (Beaudet and Hawryshyn, 1999;Cronin and Jinks, 2002;Shand, 1993;Shand et al, 1999). Visual changes resulting from chromophore replacement also occur in adult animals in response to changes in temperature and diurnal light (Cronin and Hariyama, 2002;Saszik and Bilotta, 1999;Suzuki et al, 1985;Tsin and Beatty, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the replacement A292S resulting in blue shifts of RH1 pigments has occurred several times during the 400 million years of vertebrate evolution (26,59,60). In the present study, however, we have demonstrated that the same replacement has occurred in cichlids over a very short evolutionary period of a few million years, although several amino acid positions are known to shift the max of RH1 pigment (26).…”
Section: Supporting Materials and Methods)mentioning
confidence: 99%